Damage and energy absorption behaviour of composite laminates under impact loading using different impactor geometries - Ding, Yuzhe; Liu, Jun; Hall, Zoe E. C.; Brooks, Richard A.; Liu, Haibao; Kinloch, Anthony J.; Dear, John P. (Elsevier, 2023)
The present paper compares the damage and energy absorption behaviour of composites subjected to low-velocity impact using different frontal geometries for the impactor, with the composites possessing a layup of [02/902]2s. In this study, the rigid impactors with either round-nosed or flat-ended frontal geometry are employed to perform drop-weight tests at various impact energies ranging from 10 to 30 J. The measured loading response and energy absorption are analysed and compared. Additionally, the types and extent of impact-induced damage in the composite specimens are assessed via ultrasonic C-scan, optical microscopy (OM) and scanning electron microscopy (SEM) studies. It is shown that the impact energy threshold for damage initiation is greater than 20 J when using the flat-ended impactor but is less than 10 J when using the round-nosed impactor. In both cases, delamination initiates between the plies in the composite laminate. However, for the flat-ended impactor, the damage behaviour of the fibres exhibits kinking fracture, which differs from the pull-out fibre-fracture caused by the round-nosed impactor. These differences in behaviour are attributed to impactor/composite contact geometry effects which leads to different extents of indentation damage, which in turn directly affects the degree of delamination and fibre damage in the composite.
Keywords: Composite laminates; Low-velocity impact; Impactor geometry; Ultrasonic C-scan; Scanning electron microscopy (SEM)